ANALISIS PERSYARATAN SUBSTANTIF, TEKNIS DAN ADMINISTRATIF DALAM RANGKA PENERAPAN POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH : STUDI PADA 10 PUSKESMAS DI KABUPATEN MADIUN - Zakiy, Muhammad (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aim to describe the evaluation of Puskesmas in Kabupaten Madiun to implementing Financial Management Role of Badan Layanan Umum Daerah.. This research uses qualitative method and case studies approach, with 10 Puskesmas in Kabupaten Madiun as the reasearch object. Data for evaluate is obtained from questionnaire, documentation, dan archival footage. This evaluation use questionnaire analysis to BLUD commitment, and evaluate the substantive, technical, and administrative requirements. The results indicataes that the commitment belong to 10 Puskesmas candidate of BLUD is fairly high. Furthermore, the evaluation results of substantive, technical, danadministrative reqirements that proposed by Puskesmas candidate of BLUD inidicates that Puskesmas is deserve to implementing financial management role of BLUD, Keywords: Evaluation, Badan Layanan Umum (BLU), Puskemas, Commitment, Substantive, Technical, dan Administrative requirements.